2021
DOI: 10.3389/fphar.2021.728614
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into the Beneficial Role of Lactiplantibacillus plantarum Supernatant Against Bacterial Infections, Oxidative Stress, and Wound Healing in A549 Cells and BALB/c Mice

Abstract: Lactiplantibacillus plantarum MTCC 2621 is a well-characterized probiotic strain and is reported to possess many health benefits. However, the wound healing potential of this probiotic is yet to be explored. Here, we have assessed the antibacterial, antioxidant, and wound healing activities of cell-free supernatant of Lactiplantibacillus plantarum MTCC 2621 (Lp2621). Lp2621 exhibited excellent antibacterial activity against the indicator bacteria in the agar well diffusion assay. Lp2621 did not show any hemoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 46 publications
2
22
0
1
Order By: Relevance
“…Clone formation assay was performed to explore the inhibitory ability of different preparations in the growth of tumor cells [ 57 ]. A549 cells were inoculated into 6-well plates (500 cells/well), with the treatment of KA, KA-NLC, HA 20 -KA-NLC, and HA 130 -KA-NLC for 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…Clone formation assay was performed to explore the inhibitory ability of different preparations in the growth of tumor cells [ 57 ]. A549 cells were inoculated into 6-well plates (500 cells/well), with the treatment of KA, KA-NLC, HA 20 -KA-NLC, and HA 130 -KA-NLC for 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, topical administration of L. plantarum accelerated the healing of chronic diabetic foot ulcers and infected burn wounds by altering infection, angiogenesis, macrophage phenotype, and neutrophil response [ 12 , 13 ]. It was also found that L. plantarum supernatant has protective effects against bacterial infection, oxidative stress, and wound healing [ 14 , 15 ]. According to the studies mentioned above, probiotics and their metabolites may be able to treat bacteria that are resistant to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, this bacterial strain and its metabolome mediate the production of both anti-inflammatory IL-10 and pro-inflammatory cytokines, such as IFN-γ, IL-1β, IL-2, IL-6, IL-10, IL-12, IL-17 and TNF-α [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Heat-inactivated or live L. plantarum or its supernatants could also promote skin wound healing, while simultaneously downregulating fibrotic disposition [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%